TALENT RETENTION STRATEGIES IN THE POST-PANDEMIC WORKFORCE: A MULTIGENERATIONAL STUDY - Diana Widyastika; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The post-pandemic era, marked by the "Great Resignation," has fundamentally altered the employee-employer contract, making talent retention a paramount challenge. This review investigates effective retention strategies for today's multigenerational workforce. Synthesizing contemporary literature, it identifies a shift from transactional benefits to a holistic employee experience centered on flexibility, well-being, and purpose. However, a critical analysis reveals that a uniform approach is ineffective; key retention drivers—such as flexibility and career development—are prioritized differently across Baby Boomers, Gen X, Millennials, and Gen Z. Furthermore, significant implementation gaps, including workplace inequities and internal mobility barriers, undermine these strategies. The study concludes that organizations must adopt segmented, agile retention frameworks that acknowledge generational preferences while strengthening universal fundamentals like fair compensation and authentic leadership. This nuanced approach is essential for building a resilient and stable workforce in the new world of work.